2009
DOI: 10.1007/s12541-009-0061-9
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing process of copper microgrooves utilizing a novel optical fiber-based laser-induced etching technique

Abstract: NOMENCLATURE P = laser power V = scan speed of the laser beam C= etchant concentration G = minimum gap between the workpiece and the fiber tip

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The laser beam is launched into a multimode optical fiber with a core diameter of 105 µm by using a 5× objective lens and directly delivered to the workpiece through the optical fiber. 13,14 Owing to the optical fiber as a low loss light waveguide, no optical elements are required in the laser beam path, resulting in a simple experimental setup. The one end of the optical fiber is stripped off to be used as a machining tool.…”
Section: Methodsmentioning
confidence: 99%
“…The laser beam is launched into a multimode optical fiber with a core diameter of 105 µm by using a 5× objective lens and directly delivered to the workpiece through the optical fiber. 13,14 Owing to the optical fiber as a low loss light waveguide, no optical elements are required in the laser beam path, resulting in a simple experimental setup. The one end of the optical fiber is stripped off to be used as a machining tool.…”
Section: Methodsmentioning
confidence: 99%
“…Machining processes that use microorganisms to remove metal from a workpiece, also known as biomachining, are considered more environmentally friendly than other means of removal. [2][3][4]15 Some advantages of using microorganisms include low energy consumption, high energy efficiency, and low cost. 5 Moreover, because metabolic microorganisms are utilized, no damaged layer or heat-affected zone is generated in the machined surface.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Suman [7] modelled surface tension gradient for grooved MHPs, analyzed the impacts of surface tension gradient on heat pipes' performances from the perspectives of working fluid's curvature radius, pressure and velocity, and concluded that heat transfer performances can be greatly enhanced by affixing appropriate surfactant or surface charge, which can decrease surface tension gradient of working fluid in heat pipes. Oh et al [8] proposed a technique of laser-induced thermochemical etching, which can help fabricate triangle grooves with smooth surface in copper pipes' inner wall. Xin et al…”
mentioning
confidence: 99%